Positive-real truncated balanced realization based frequency-weighted model reduction - Kumar, Deepak; Zulfiqar, Umair; Sreeram, Victor; Imran, Muhammad; Wan Muda, Wan Mariam; Haja Mohideen, Ahmad Jazlan; Wu, Ai Guo (IEEE, 2020)
In this paper, a new frequency-weighted positive real balanced truncation technique is presented by using a combination of frequency-weighted model reduction with the positive real-truncated balanced realization (PR-TBR). The proposed technique yields passive reduced-order model for a given passive high order model with single-sided weighting only. The simulation results of the proposed technique are shown by using an example problem of RLC ladder network.